MODELING AS TRAINING METHOD IN INFORMATION TECHNOLOGIES - Marina V. Yadrovskaya (Advanced Engineering Research, 2012)
Modeling is considered a powerful means of cognition. It is used, as a rule, as one of the effective training methods and devices. The performed analysis has resulted in determining the usage patterns and the advantages of the modeling method application as a training method in the information technologies. It is found out that the application of the modeling method in the information technologies at the technical university permits to develop information competencies including so important for a contemporary specialist modeling methodological knowledge.